“Centralized and Popularized” Evolution of the West Lake Space in Northern Song Dynasty and its significance - J. Shen; L. Zhang; Y.D. Zhang (International Association of Lowland Technology, 2018)
This paper discusses characteristics of spatial change of Lake Space, and its significance to the entire Space of West Lake against a backdrop of the rise of citizen stratum in Northern Song Dynasty. The evolution of Lake Space is analyzed from two perspectives: physical form and cultural form. Multidimensional transformation of physical form enriches the spatial hierarchy, and enables special elements to expand from a previously isolated point to currently-integrated multiple elements with points and lines echoed and imaginary and actual elements combined. Cultural form breaks up the singleness dominated by religious culture, and expands to the coexistence of various cultural elements such as release, seclusion, religion and tourism. The evolution of Lake Space in Northern Song Dynasty has exerted far-reaching influence on West Lake Space. “Centralized Evolution” of West Lake completed in Northern Song Dynasty, its focus evolved from “mountain space” to “mountain space and lake space”, and its space radiation layout from “inward radiation from mountain space” to “outward radiation from lake space”. Lake space was no longer just a geometric center of the West Lake, but also become its real core space.